2008
DOI: 10.1007/s12192-008-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based detection of Pol III-transcribed transposons and its application to the rodent model of ultraviolet response

Abstract: Cellular levels of RNAs containing transposable elements increase in response to various stresses. Polymerase III (Pol III)-dependent transcripts of transposons are different from transposon-containing RNAs generated by read-through Pol II-dependent transcription. Until now, Pol III transcripts were detected by primer extension followed by time-consuming gel electrophoresis. In this paper, we describe a more sensitive PCR-based method for the selective detection of Pol III-transcribed RNAs. The method is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Some studies have indicated that UV radiation can mobilize TEs (Kuan et al 1991;Eichenbaum and Livneh 1998;Qüesta et al 2010Qüesta et al , 2013Myakishev et al 2008;Morales et al 2003). The only reported mobilization in the Tc1/mariner superfamily is that of Ogasawara et al (2009) for the fungus A. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that UV radiation can mobilize TEs (Kuan et al 1991;Eichenbaum and Livneh 1998;Qüesta et al 2010Qüesta et al , 2013Myakishev et al 2008;Morales et al 2003). The only reported mobilization in the Tc1/mariner superfamily is that of Ogasawara et al (2009) for the fungus A. oryzae.…”
Section: Discussionmentioning
confidence: 99%